Perceptions of Czech Rural Life by its Inhabitants in Connection to Tourism - Renata Klufová; Marek Šulista (DETUROPE)
Rural tourism in the EU Member States is an important segment of the tourist market. Rural areas achieve multiple benefits from developing rural tourism. From this point of view, rural tourism revitalises rural areas, decreases depopulation, enables the valorisation of economic resources, etc. On the other hand, rural tourism highlights, and thus preserves, the cultural, environmental, natural, traditional, and historical characteristics of a specific rural area. In this way, the regional diversity, authenticity, and recognisability are maintained in the united Europe, which provides a competitive advantage to the European Union's tourist market. However, bottom-up initiatives within the local communities and appropriate attitudes towards the development of tourism are important. The aim of this contribution is to evaluate the perceptions of Czech rural life by its population with a focus on tourism. The evaluation is a part of a broad-based questionnaire survey aimed at the assessment of different aspects of rural life. The perceptions of tourism are monitored in conjunction with other characteristics of self-assessment by respondents and their assessment of the villages in which they live. Classical dependencies of the obtained data from the survey were analysed at first, and then multidimensional statistical methods (CATegorical Principal Component Analysis, cluster analysis) were used in the hypothesis testing of the interference of "hard" and "soft" factors of the rural development. This comparison confirms that "hard" and "soft" development factors really affect each other. Therefore, rural development strategies need to be designed so that both sets of factors are in line with the aim of synergy. The hard localization and realization factors themselves, without supporting the development of soft factors, do not have the desired effect.